Beijing direct investment to its neighbors: A pollution haven or pollution halo effect?. (1st December 2019) - Wang, Hao; Dong, Changgui; Liu, Yi
Abstract: Beijing-Tianjin-Hebei (BTH) in China is a key metropolitan area with high development imbalance and serious environment pollution spillovers. While foreign direct investment (FDI) only accounts for 5% of local GDP in this region, Beijing direct investment (BDI) to its two neighbors starts to play an important role in promoting integrated development and tackling regional environmental problems ever since 2014. In this paper, we construct a unique dataset on 157 county-level administrative units in the BTH area as a host of BDI, and test if BDI has resulted in a pollution haven effect or a pollution halo effect in the industrial sector. Results show that BDI has been conducive to reducing industrial pollution emissions in the host administrative units, a pollution halo effect and win-win situation for both Beijing and its neighbors. However, FDI is estimated to have a pollution haven effect for certain industrial pollutants or insignificant. Our results stand with several robustness checks, heterogeneity analysis and a further test on reverse causality, and point to a new avenue for regional environment improvement via environmental friendly and sustainable industrial relocation.